Polymer-Encased Nanodiscs and Polymer Nanodiscs: New Platforms for Membrane Protein Research and Applications - Chen, Angela; Majdinasab, Elleana J.; Fiori, Mariana C.; Liang, Hongjun; Altenberg, Guillermo A. (Frontiers in Bioengineering and Biotechnology, 2020)
Membrane proteins (MPs) are essential to many organisms’ major functions. They are notorious for being difficult to isolate and study, and mimicking native conditions for studies in vitro has proved to be a challenge. Lipid nanodiscs are among the most promising platforms for MP reconstitution, but they contain a relatively labile lipid bilayer and their use requires previous protein solubilization in detergent. These limitations have led to the testing of copolymers in new types of nanodisc platforms. Polymer-encased nanodiscs and polymeric nanodiscs support functional MPs and address some of the limitations present in other MP reconstitution platforms. In this review, we aim to provide a summary of recent developments in the use of polymers in nanodiscs.